When the Same Isn’t Similar: Herménégilde Chiasson in English - Nichols, Glen (TTR)

(untitled) (Association canadienne de traductologie, 2009)
Out of Herménégilde Chiasson’s many French publications, only seven are available in English translation. While these translations are very conservative and consistent in their attempt to transcribe “accurately” the source texts, a closer study reveals the fallacy of this approach in terms of understanding either the texts or their implications for the reading of cultures. Other than generally minor errors or compromises, the translations are “faithful” to the sources, textually, but this is hardly significant or sufficient, other than in reinforcing clichés about Canadian binary nationalism. However, the participation in different literary systems, their paratextual presentations, the particular selectivity of these works over others in Chiasson’s corpus, and the traditional critical reactions all point to the construction of a very different, more passive and “universalized” Acadian author in English. A “multipolar” approach, borrowed from Comparative Literature and Translation Studies, means these differences can be revealed, explained, and understood. Even though the results may not suit a comfortable view of Canadian society, the resistance to the erasure of difference is an important role for our disciplines in training better readers, who are more open to difference and multiplicity in cultural production.